Augmentation de la pauvreté en Angleterre depuis 2010 : crise ou idéologie ? - Raphaële Espiet-Kilty (Revue Française de Civilisation Britannique)
In the aftermath of the financial crisis of 2008 the Conservative leader of the Opposition – David Cameron – delivered a speech in Cheltenham revolving around the theme of rupture: between the neoliberal Conservatism of the Thatcherite right-wing of the Party and his own more compassionate brand of Conservatism; rupture of the cycle of growth caused by the crisis and by the supposedly irresponsible policies of the New Labour government. To give credence to his compassionate Conservatism Cameron proposed to tackle poverty by building a Big Society in “The Age of Austerity” which, according to him, was the sensible response to the crisis and to the public deficit which was increasing under Brown. In the summer 2014, the Trussel Trust published a controversial report claiming that the number of people living in food poverty had increased from 346,992 in 2012-2013 to 913,138 a year later. Was this increase the consequence of the crisis or of the austerity policies introduced by the coalition government elected in May 2010? The aim of this paper is two-fold: first to demonstrate that in spite of the Department for Work and Pensions (DWP)’s rebuttals, the increase in the number of people living in food poverty reflects an increase in absolute poverty caused in part by the coalition government’s austerity; second, that the crisis was a pretext for the introduction of welfare cuts. The coalition government would have reformed the welfare state regardless, in accordance with fundamental conservative and neoliberal principals.